General characteristics and structure of environmental risks in the subsoil use sphere (Journal of actual problems of jurisprudence, 2019)
This article reviews the essence, types and structure of environmental risks in the subsoil use sphere. It hasbeen defined that a variety risks associated with the environment is covered by the single term which is“environmental risks”. The environmental risk is understood as a beforehand evaluated probability and anextent of hazard that in any man-made intervention into the environment disturbances may arise that can beunfavorable for further functioning and existence of environmental systems both in the man-made effect zoneand beyond its limits. It has been demonstrated that works executed in the subsoil use sphere considerablyaffect the environment. On the basis of researches performed that author provides a comprehensive definitionof the “environmental risk” term, formulates its main characteristics and structural elements.Keywords: environmental risks, environment, land, land use, insurance risks.